Deficiencies in Quality Assurance while Procuring and Disributing Drugs in Karnataka - CAG of India (CAG of India)
Poor quality assurance by the Karnataka State Drugs Logistics and Warehousing Society resulted in distribution of non-standard quality drugs. Besides, the Society did not recover INR 2.11 crore being the cost of these non-standard quality drugs.